Analisis Perbandingan Kinerja Perusahaan Otomotif dan Komponen Yang Tercatat Di Bursa Efek Indonesia Dengan Menggunakan EVA, REVA, FVA, Dan MVA - Rahadjeng, Erna Retno (Benefit: Jurnal Manajemen dan Bisnis, 2019)
The use of measuring instruments for Economic Value Added (EVA), Refined Economic Value Added (REVA), Financial Value Added (FVA), and Market Value Added (MVA) simultaneously in measuring the company's financial value-added performance is realistic. and support the presentation of financial statements, so that users of financial statements such as corporate leaders and investors can easily make decisions. This study took samples from Automotive companies listed on the Indonesia Stock Exchange (IDX) in the 2012-2016 period. Data collection was carried out by purposive sampling for four periods through the approach of performance measurement methods based on value added, showing financial performance that was significantly different from year to year. The four methods of measuring financial performance are EVA, REVA, FVA and MVA to determine the performance of automotive companies. The method used in this research is descriptive method. Based on the results of data analysis it is known that financial performance seen from the value of EVA, REVA, FVA and MVA has a positive value, meaning that the company provides added value to investors. It is suggested from the results of research to the management of the company to pay attention to the components that can still provide added value to shareholders, and for investors are expected to continue to invest in companies that have added value. Finally, suggestions for further researchers to continue to do research on other companies go public by measuring value added.